Lodging in soybean (Glycine max) as influenced by growth habit and other traits - RAJKUMAR, RAJKUMAR; SINGH, DEVVRAT; MURLIDHARAN, POOJA (The Indian Journal of Agricultural Sciences, 2014)
Thirty soybean varieties were grown for consecutive two years to study how the growth habit, stem diameter and plant height influence the lodging in soybean. Plant height was found to be significant and positively correlated with lodging and growth habit. The reduced plant height showed increased resistance to lodging in soybean. Growth habit was significantly correlated with plant height, nodes and lodging. Stem diameter was not significant with any of the traits studied. Although the determinate varieties were shorter, equivalent yields were produced by determinate and semi-determinate. No significant correlation was established between growth habit and yield; however, JS 95-60 was the highest yielder followed by JS 335, RKS 18, JS 93-05, MAUS 71, NRC 37 and PS 1225. Semi-determinate varieties were comparatively taller than determinates and susceptible for lodging.